PENGARUH SUBSTITUSI TEPUNG UBI JALAR UNGU TERHADAP KUALITAS ROTI TAWAR - Yuliandari, Vebi; Ruaida, Ruaida; Holinesti, Rahmi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
Purple sweet potato flour as a food ingredient has not been optimally used in the diversification of food processing, while the purple sweet potato flour can be an alternative to replace some of the flour as the main ingredient of bread This study aimed to analyze the effect of substitution of purple sweet potato flour as much as 5 %, 10% and 15% of the wheat flour used for external quality and internal quality as well as hedonic on bread. The research is a pure experiment with completely randomized design method using three times replication with 30 panelists. The results showed that the purple sweet potato flour substitution effect on the external quality (volume, rectangular shape and form neat) and internal quality (soft texture and smooth texture) which is generally the best value found in the treatment of 5% (X1) and the effect on the quality internal (pore color, aroma of purple sweet potato and taste of purple sweet potato) are generally the best value found in the treatment of 15% (X3), but had no effect on the quality of the external (skin color) and internal quality (aroma yeast). In the hedonic test (favorite) the panelists preferred the substitution of 5% (X1) than the other treatments.Keywords: substitution, purple sweet potato flour, white bread quality